Bioaccumulation of zinc and cadmium in freshwater fishes - Madhusudan, Sharma; _, Liyaquat; _, Fatma; Nadim, Chishty (Indian Journal of Fisheries, 2011)
Bioaccumulation of zinc and cadmium was estimated in freshwater fishes viz. Labeo rohita, Catla catla, Channa punctatus and Poecilia reticulata after acute and sublethal exposure to different concentrations of these metals and zinc smelter effluent. These observations were related with acute and chronic toxicity results. A linear relationship of zinc and cadmium accumulation with exposure concentration was noted in the case of Labeo fry. But a regular pattern of accumulation was lacking during exposure to effluent. The study was further extended to analyze zinc and cadmium in tissues of exposed fishes after longterm sub-lethal chronic exposure. An attempt was also made to study intake, persistence and elimination of cadmium in Labeo rohita. Present findings revealed that liver and kidney are the prime sites of metal accumulation and heavy metal load in the muscles was far low as compared to these organs. In the muscles of Labeo rohita and Catla catla, 0.2925 and 0.2930 mg Zn/g was accumulated respectively. These values were low as compared to 0.7888 and 1.748 mg Zn/g accumulated by livers of these fishes. Cadmium exhibited different organ wise retention pattern showing maximum accumulation in kidneys of exposed Labeo rohita, Catla catla and Channa punctatus as evident from 0.1558, 0.1606 and 0.07296 mg Cd/g respectively.